2021
DOI: 10.1017/s0144686x20001968
|View full text |Cite
|
Sign up to set email alerts
|

Linking people and activities through community mobility: an international comparison of the mobility patterns of older drivers and non-drivers

Abstract: Community mobility using private and public transportation is important for maintaining health, social participation and living well in later life. This international cross-sectional cohort study (N = 246) reported on the health and driving status of older adults from seven countries where the mobility patterns of drivers and non-drivers were compared in terms of city and rural areas, weather, as well as their respective differences in the number of out-of-home places accessed and quality of life. Older adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The term'life space' , as used in gerontology, relates to mobility and navigating outside one's home to reach the places where participation in the community unfolds [9] The construct of community as defined by an individual, implies freedom of association and locational choices [10]. Thus, community mobility comprises navigating of life space in order to reach places that are meaningful, fostering a sense of belonging, and supporting social participation [11] by engaging in occupations that are of value to the person [12]. Community mobility is a key determinant of health and quality of life [13] that can be affected by a wide variety of factors ranging from personal, internal factors to external and global factors.…”
Section: Open Accessmentioning
confidence: 99%
“…The term'life space' , as used in gerontology, relates to mobility and navigating outside one's home to reach the places where participation in the community unfolds [9] The construct of community as defined by an individual, implies freedom of association and locational choices [10]. Thus, community mobility comprises navigating of life space in order to reach places that are meaningful, fostering a sense of belonging, and supporting social participation [11] by engaging in occupations that are of value to the person [12]. Community mobility is a key determinant of health and quality of life [13] that can be affected by a wide variety of factors ranging from personal, internal factors to external and global factors.…”
Section: Open Accessmentioning
confidence: 99%
“…For example, Kaplan and Newsome (2001) and Merchant et al, (2007) propose that the east-to-west gradient in physical activity levels in Canada is related to a more temperate climate in British Columbia (western Canada), as well as other cultural and environmental differences (Kipp et al, 2019). Additional studies suggest that older adults in rural and remote regions are vulnerable to severe weather conditions (Chan & Ryan, 2009), and seasonal (Turrisi et al, 2021) and climatic changes (Kipp et al, 2019), with obvious implications for transportation and travel (Unsworth et al, 2021). An extensive review of unmet travel needs by Luiu et al, (2017) found that at least one-third of older people, especially women and adults 75 years old and above, were affected by limited transportation options.…”
Section: Tablementioning
confidence: 99%
“…Government/policy related level of influence The comparison of the mobility patterns of older adults by Unsworth et al, (2021) attests to the complexity and interconnections embedded in providing adequate transportation and infrastructure to support active living for older adults. At a neighbourhood level, local government initiatives are critical (Dechaine & Witcher, 2007), and may involve clearing sidewalks of snow build-up and debris during winter (Belon et al, 2014), extending access to recreational facilities (Belon et al, 2014), maintaining and expanding physical activity opportunities (Paluck et al, 2006), and financial assistance and sponsorship for small community-based organisations (Paluck et al, 2006).…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations